(untitled) (International Journal of Engineering and Computer Science, 2014)
Disruption-Tolerant Networks (DTNs) deliver data to the collection of intermittently connected nodes. In traditional networks, malicious nodes within a DTN may try to attempt a data destruction or delay in transmit the data to its destination. In this paper, the flooding attack is focused and provides possible solutions for secure communication. Many existing algorithms for secure routing require security mechanisms like public key infrastructure (PKI), which is difficult to deploy in a DTN. This paper proposes a secure communication model to transmit the packet from source to destination with PKI. A rate limit certificate process is presented to check for authenticated user. Here, Claim carry and check technique is used to overcome the difficulties in existing to count all the packets or replicas sent by a node due to the lack of communication infrastructure. Also the pigeonhole principle is used to guarantee that an attacker will make inconsistent when they joined in routing. The implementation results shows that the proposed Secure Communication Model for DTNs results better claim accuracy, less execution time and reduced transmission cost than the existing credit-based approach